EFFECT OF WORK ENVIRONMENT, LEADERSHIP, COMPENSATION AND EMPLOYMENT TRAINING TO EMPLOYEE INVOLVEMENT - S, Antony (Program Sarjana Manajemen Universitas Internasional Batam, 2019)
This study was conducted with the aim to determine the effect of the work environment, leadership, compensation and work training variables on employee involvement variables in star hotels in Batam. This research was conducted using a survey method through a questionnaire to 380 respondents, namely employees of five-star hotels in Batam. After being distributed directly to respondents, the questionnaire was collected and managed to get 340 questionnaires filled out completely and then the authors tested the regression data using the SPSS program. From the results of data processing with SPSS it is known that there is a relationship in all variables studied. Based on the results of this study, the relationship between work environment variables, leadership, compensation and work training in employee attachment variables is known, so it is expected that star hotel management can pay attention to the variables studied earlier and manage employee attachments as one of the added values ??and advantages of the hotel.